Tidying up the small-leaved Clusia taxonomy: description of Clusia nanophylla (Clusiaceae), a new tree species from Panama and comments on its previously used names - Jorge Aranda; Ernesto G. Campos-Pineda; Joana S. Sumich; Aurelio Virgo; Milton García; Klaus Winter; Manuel Luján; Barry Hammel (Kew Bulletin, 2025)
Summary Clusia nanophylla (Clusiaceae), a new tree species from Panama, is described. The species has the smallest leaves recorded so far within the genus. Its staminate flowers have 17 or 18 free stamens and the pistillate flowers present 3 petals, sepals, staminodes, stigmas, styles and carpels. The species is known from one location, and according to IUCN criteria, is here assessed as threatened. Comments on two invalid names that have been used for this taxon are included.